"I knew that I wasn't cis, I knew that, but I didn't know exactly": Gender identity development, expression and affirmation in youth who access gender affirming medical care. Issue 3 (2nd July 2020) - Pullen Sansfaçon, Annie; Medico, Denise; Suerich-Gulick, Frank; Temple Newhook, Julia
Abstract: Background: Research about gender identity development is still in its infancy, especially among youth who experience gender dysphoria and are accessing gender-affirming medical care. Aims: This article contributes to the literature on how gender identity and gender dysphoria is experienced, expressed and addressed by youth who have started, or are just about to start, a gender-affirming medical intervention. Methods: The project draws from qualitative interviews with 36 trans children and youth of different ages and stages of puberty. The data were collected in three specialized Canadian clinics that offer gender-affirming care and they were analyzed through inductive thematic analysis. Results: Two interlinked dimensions of the youth's lives allow meaning-making of their gender identity: 1) internal or personal and 2) interactional or social processes. Careful analysis reveals three gender identity development pathways that may be taken by youth, from early questioning to the affirmation of their gender identity. A discussion of current models of gender identity development and their limitations concludes the article.